Antimicrobial potential of Carica papaya, Ipomoea aquatica, Alpinia galanga and Piper betle against the aquatic microbials - GINA SAPTIANI; ESTI HANDAYANI HARDI; CATUR AGUS PEBRIANTO; AGUSTINA AGUSTINA; FIKRI ARDHANI (Nusantara Bioscience, 2016)
Abstract. Saptiani G, Hardi EH, Pebrianto CA, Agustina, Ardhani F. 2016. Antimicrobial potential of Carica papaya, Ipomoea aquatica, Alpinia galanga and Piper betle against the aquatic microbials. Nusantara Bioscience 8: 252-257. This research was aimed to investigate the antimicrobial potential of the leaves extract from Carica papaya, Ipomoea aquatica, Piper betle and Alpinia galanga stem against Aeromonas hydrophila, Pseudomonas sp., Escherichia coli, and Saprolegnia spp.; the pathogenic microbes in aquatics. These plants were dried and extracted with water and ethanol, separately. The extract was then tested for its inhibition effect to the microbial by in vitro agar disc diffusion (ADD) at the concentration of 100, 200, 400, 600, 800, and 1,000 ppm and minimal inhibitory concentration (MIC) at the concentration of 600, 800, and 1,000 ppm. The result showed that water or ethanol extract f of plants showed potent inhibitor against the aquatic microbial. The ethanol extract of P. betle showed the highest inhibition at 800 ppm, with inhibition zones to A. hydrophila, and Pseudomonas sp. 12.3 mm, E. coli, and Saprolegnia spp. 12.7 mm. One thousand ppm ethanol extract of P. betle could inhibit the best microbes growth using MIC method to A. hydrophila 189.7 cfu/mL, Pseudomonas sp. 253.0 cfu/mL, Saprolegnia spp.169.3 cfu/mL, and 800 ppm to E. coli 172.7 cfu/mL.